Niger : Staff Report for the 2014 Article IV Consultation and Fourth and Fifth Reviews Under the Extended Credit Facility Arrangement and Request for Waiver of Nonobservance of Performance Criteria and Modification of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2015)
This 2014 Article IV Consultation highlights that Niger's overall macroeconomic performance has been broadly satisfactory. After the economic slowdown in 2013 owing to the regional security situation and adverse climatic conditions, economic growth has rebounded in 2014. Inflation has been contained, in part owing to the government's efforts to improve food security and the functioning of food markets. However, program performance has been mixed, as a combination of unexpected security and food expenditures and a shortfall in external financing have strained fiscal management. In the near term, containing the fiscal deficit through measures to improve tax policy and administration, reform customs administration, and reduce exemptions is essential to ensure sustainability.